2013
DOI: 10.4236/ajac.2013.49060
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fatty Acid Profiles during Supercritical Transesterification of Conventional and Non-Conventional Feedstocks: A Review

Abstract: In this study, the influence of fatty acids of both conventional and non-conventional oils in supercritical transesterification method has been reviewed. Literature on oils such as moringa oleifera, manketti, croton megalocarpus, palm and soybean has been reviewed to establish an understanding of the supercritical transesterification that employed methanol as alcohol. This study reveals that lower yield of methyl esters is observed when higher temperatures are employed in oils that are highly dominated with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…Based on the GC analysis, it was found that MME contained 18.3% saturated FAs and 81.7% unsaturated FAs compared to the values reported previously i.e. 17.2% saturated FAs and 82.9% unsaturated FAs by Kafuku and Mbarawa (2013) and 27.4% saturated FAs and 72.8% unsaturated FAs by Ruttoa and Enweremadu (2011). It can be concluded that MME, PEME and CIME are mainly dominated by unsaturated FAs while COME is dominated by saturated FAs.…”
Section: Error Analysismentioning
confidence: 60%
See 4 more Smart Citations
“…Based on the GC analysis, it was found that MME contained 18.3% saturated FAs and 81.7% unsaturated FAs compared to the values reported previously i.e. 17.2% saturated FAs and 82.9% unsaturated FAs by Kafuku and Mbarawa (2013) and 27.4% saturated FAs and 72.8% unsaturated FAs by Ruttoa and Enweremadu (2011). It can be concluded that MME, PEME and CIME are mainly dominated by unsaturated FAs while COME is dominated by saturated FAs.…”
Section: Error Analysismentioning
confidence: 60%
“…Physico-chemical properties of MME Table 5 shows the physico-chemical properties of the produced MME in comparison with those of the CIME, COME and PEME (Ruttoa and Enweremadu, 2011;Atabani et al, 2013a;Kafuku and Mbarawa, 2013;Atabani et al, 2014). Having considered the data presented in Tables 3 and 4 for CMO and MME, it can be seen that the kinematic viscosity was successfully reduced from 132.75 to 8.03425 mm 2 /s, refractive index from 1.487 to 1.4698, and density at 40 °C from 925.1 to 887.8 kg/m 3 .…”
Section: Fatty Acid Composition (As % Methyl Esters)mentioning
confidence: 99%
See 3 more Smart Citations